HUBUNGAN KONSEP DIRI DENGAN KECEMASAN NARAPIDANA PADA RUTAN KELAS II B MAJENE - Nurfadilah Nurfadilah; Munadiah Wahyuddin (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Al Asyariah Mandar, 2020)
The concept of self is an individual's conceptualization of himself directly this self-concept affects self-esteem and one's feelings towards himself. Self-concept is divided into 2 namely positive self-concept and negative self-concept when an individual has a positive self-concept, his anxiety will be low whereas when an individual has a negative self-concept, his anxiety will be high. Prisoners are individuals who lose freedom where inmates experience anxiety which tends to be depressed due to their inability to adjust. The purpose of this study was to determine the relationship between self-concept and prisoner anxiety. This type of research is observational analytic research with a cross-sectional study approach with the method of Simple Random Sampling. The instrument used was a questionnaire with a Likers Scale and HARS Scale. The sample in this study was 57 inmates. Based on the results of the Chi-Square analysis showed that the hypothesis tested in the study was rejected with a significant value of 0.671 which means greater than 0.05 (p> 0.05). It can be concluded that there is no significant relationship between self-concept and prisoners' anxiety in Majene Class II Prison. Suggestions for further researchers are to be able to add factors related to self-concept while adding samples to get more significant results.